Experimental study on heat transfer and pressure drop in a channel with triangular v-ribs - Jansangsuk, Dumri; Khanoknaiyakarn, Chitakorn; Promvonge, Pongjet (My University, 2010)
The paper presents an experimental study on heat transfer and pressure drop characteristics in a rectangular channel fitted with periodic triangular v-pattern ribs. The ribs are tested for pointing downstream (v-down) to the flow. The channel has an aspect ratio (width to height ratio), AR = 10 and height, H = 30 mm; the rib-to-channel height, e/H = 0.1, 0.2, and 0.3; the rib pitch to channel height, PR=P/H = 3 and 4; the attack angle (α) of 30° relative to the flow direction. The experiment has been conducted by varying air flow velocity in order to adjust Reynolds number range from 5000 to 20,000. The upper plate of channel is uniformly heated as a constant heat flux while the whole test section is covered with insulation to reduce heat loss to surroundings. These boundary conditions correspond closely to those founded in solar air heaters. The experimental results show a significant effect of the presence of the ribs on the heat transfer rate and pressure drop over the plain channel. The measured data indicates that the triangular v-type rib with e/H = 0.3 and PR =3 yields higher heat transfer rate in terms of Nusselt number, Nu, and the pressure drop in the form of friction factor, f, than the others and also much higher than the smooth wall channel.
Keywords: Heat transfer; Pressure drop; Rectangular channel; Triangular v-type rib